The Physiological, Behavioral and Psychological Impact of Excessive Use of Smart Devices in Children - Hassanein Fadel Mohammed; Hadeel Thaer Ahmed Al-Najem (Indonesian Journal on Health Science and Medicine, 2026)
General Background: The rapid expansion of digital technology has made smart devices an integral part of daily life, including among children. Specific Background: Increasing exposure to smartphones has raised concerns regarding physical, psychological, and behavioral outcomes in early childhood. Knowledge Gap: Limited integrated evidence exists on how excessive device use simultaneously relates to health, sleep, behavior, and educational aspects in children. Aims: This study aims to examine the effects of excessive smart device use on children’s health, sleep patterns, behavior, and educational engagement. Results: Findings indicate that 43.5% of parents observed vision problems, 56.9% reported sleep disturbances, and notable proportions identified behavioral changes such as irritability and aggression. Additionally, 44% reported eye-related issues and a considerable number of children experienced neck or back discomfort. Educational use of devices was inconsistent, with many parents reporting no observable improvement in learning outcomes. Novelty: The study integrates multiple dimensions of child development within a single descriptive framework using parental perspectives. Implications: The findings highlight the importance of parental supervision, time regulation, and guided device use to reduce potential risks and promote balanced child development. Keywords: Smart Devices, Child Health, Screen Time, Behavioral Changes, Sleep Disturbance Key Findings Highlights High prevalence of reported visual and sleep-related disturbances among children Behavioral responses indicate dependency and emotional instability Educational utilization remains inconsistent and often unclear